Digitalization and digital transformation in schools: a challenge to educational theory? - Josef Siljebo (University of Aberdeen, School of Education, 2020)
There is an apparent lack of theoretically robust definitions of digitalization and digital transformation in educational research. This article purposes to contribute to educational research and practice by understanding digitalization and digital transformation through educational theory. The approach to the research problem was first to theoretically define digitalization and digital transformation in schools in terms of human learning and development. This perspective suggested that digitalization may be a requirement for digital transformation but not an enabler. Moreover, it suggests that digitalization and digital transformation in schools are always anchored to human learning and development. Secondly, the approach empirically tests this theoretical development via a quantitative questionnaire survey with seventeen Swedish school leaders. The data indicated the theoretical development seems to hold in school practice as well as conceptually. Limitations to the approach were discussed, and suggestions to future research of remote teaching in rural schools are given. In particular, future research is suggested to develop, contrast, and use the definition.